MANAGEMENT OF THE REGIONAL GOVERNMENT PUBLIC SERVICE DEVELOPMENT STRATEGY WITHIN THE REGIONAL SECRETARIAT OF SUBANG REGENCY - Arip Rahman Sudrajat (SEAN Institute, 2023)
This study seeks to analyze the regional secretariat of Subang Regency's strategy for the development of local government public services. This study employs a qualitative approach and descriptive methodology. Data was collected by conducting in-depth interviews with relevant officials and analyzing public services and regional strategic plans documents. The results of the study indicate that the management of the strategy for developing public services within the regional secretariat of Subang Regency has been implemented through multiple efforts, including a strategy for developing a structure, a strategy for developing or streamlining a procedural system, a strategy for developing infrastructure, a strategy for developing culture, and a strategy for developing entrepreneurship. On the basis of the findings of this analysis, it is recommended that the Subang Regency secretariat improve coordination between work units in implementing the public service development strategy, involve all existing stakeholders more actively in preparing strategic plans, and seek additional funding sources to support the implementation of the strategy. Development of public services within the Subang Regional Secretariat.